Legal Analysis of The Implementation of Child Inmates Coaching in Class II-B Correctional Institution of Langsa City, Indonesia - Wilsa Wilsa (UNIFIKASI : Jurnal Ilmu Hukum, 2018)
Republic of Indonesia Law Number 12 of 1995 concerning Corrections assets that correctional coaching is carried out based on several principles, namely: guidance; treatment and service equality; education and counseling; respect for human dignity; and guarantee to keep in touch with families and certain people. Class II-B Correctional Institution of Langsa city is an adult Correctional Institution. The purpose of this study is to analyze the implementation of child inmates coaching in Class II-B Correctional Institution of Langsa city and find out the efforts done to overcome constraints in the implementation of child inmates coaching. The method used in this research was Juridical Empirical research method that examines the implementation of normative legal behavior relating to the implementation of child inmates coaching in Class II-B Correctional Institution of Langsa city. The results showed that the implementation of child inmates coaching does not correspond to childs rights since, in addition to an over capacity of the correctional institution, child inmates do not get personality and self-reliance coaching. In conclusion, the child inmates coaching which is expected to be well implemented is far from the expectations since it does not correspond to childs rights. Therefore, it suggested that the government can immediately build a special Correctional Institution for child inmates with appropriate facilities and infrastructure since children are the next generation of a nationUndang-undang RI Nomor 12 Tahun 1995 tentang Pemasyarakatan dimana menegaskan pembinaan pemasyarakatan dilaksanakan berdasarkan beberapa asas yaitu : Pengayoman ; Persamaan perilaku dan pelayanan ; Pendidikan dan pembimbingan ; Penghormatan harkat dan martabat manusia ; Kehilangan kemerdekaan satu-satu nya penderitaan ; Terjaminnya hak untuk tetap berhubungan dengan keluarga dan orang-orang tertentu . Lembaga Pemasyarakatan kelas II-B Kota Langsa adalah lembaga Pemasyarakatan Dewasa, Tujuan penelitian ini adalah mengetahui dan menganalisis bagaimana pelaksanaan pembinaan hak-hak narapidana anak di Lembaga Pemasyarakatan kelas II-B Kota Langsa dan bagaimana upaya yang dilakukan untuk mengatasi kendala dalam pelaksanaan pembinaan narapidana anak. Metode penelitian yang digunakan dalam penulisan ini yaitu Metode penelitian yang digunakan yaitu Yuridis Empiris yaitu mengkaji mengenai implementasi ketentuan hukum normatif (perundang-undangan) yang berhubungan dengan pembinaan narapidana anak di lembaga pemasyarakatan Kelas II-B kota Langsa. Hasil penelitian pelaksanaan pembinaan narapidana anak tidak memenuhi hak-hak narapidana anak, karena selain keadaan lembaga pemasyarakatan over kapasitas, kenyataan apa yang diharapkan tidak terealisasi dengan baik, karena narapidana anak tidak mendapatkan pembinaan kepribadian dan pembinaam kemandirian. Simpulan secara faktual pembinaan narapidana anak yang diharapkan tidak terlaksana dengan baik, jauh dari harapan pemenuhan hak-hak narapidana anak., disarankan pemerintah segera membangaun Lembaga pemasyarakatan khusus anak dengan sarana dan prasarana yang layak. Mengingat anak adalah generasi yang berpotensian bagi bangsa